Qur'anic Immunity as Islamic Medicine in the Big Family of Ruqyah Aswaja - Dwi Indah Rizqi (IAT dan ILHA, UIN KH ABDURRAHMAN WAHID, 2022)
This article discusses Islamic medicine in the Ruqyah Aswaja extended family. The Ruqyah Aswaja method is a treatment that has been exemplified and explained by the Prophet SAW to people who are sick about what the apostle knows based on revelation. Ruqyah Aswaja is an activity of removing jinn, magic, and others which begins with relying on Allah's guardians and ends by offering and recognizing the essence of life. Allah SWT has sent down disease to humans, but Allah is responsible for sending down a disease. One of the functions of the Qur'an is as a healing syifa (medicine) for people who believe in various diseases, both physiological and physical.The focus of the problem studied in this article is how Islamic treatment is carried out on the large family of Ruqyah Aswaja treatment. The purpose of this paper is to explain that Islamic medicine is not limited to spiritual medicine, but can also be used for physical medicine. This research is a field research and data collection through interviews, observation, and documentation. To analyze the data, the author borrows from Sam D Gill's offer, namely the informative function and the performative function. The results of this study, the informative function shows that the text is generated from meaning and understanding through diplomas, guide books, websites and KBRA social media platforms. Meanwhile, the performative function consists of two forms, namely healing through spiritual encouragement and selling herbal medicinal products.